Perineurioma: A Rare Entity of Peripheral Nerve Sheath Tumors - Brand, Christine; Pedro, Maria Teresa; Pala, Andrej; Heinen, Christian; Scheuerle, Angelika; Braun, Michael; Antoniadis, Gregor (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Objective Intraneural perineurioma is a rare tumor entity. It is a benign, very slow growing peripheral nerve sheath tumor that typically occurs in children and young adults. Motor deficits and muscle atrophy are classic presenting symptoms, while sensory deficits are rare at the onset of the disease. Recommended treatment strategies are lacking. We have evaluated the clinical follow-up and our experience with treatment of this rare entity.Methods A total of 30 patients with intraneural perineuriomas were assessed retrospectively. Demographic data, clinical symptoms, diagnostic examinations, therapy strategies, and clinical outcome were analyzed. Descriptive statistical methods were used for evaluation.Results The mean age was 22 years. Eleven women and 19 men were affected. The lesion occurred in the area of the upper extremity in 16 patients and in the area of the lower extremity in 14 patients. The most frequently affected nerve was the sciatic nerve, followed by the radial nerve. All patients showed a motor deficit to some extent. Seventy percent (n = 21) revealed atrophy, 43.3% (n = 13) had sensitive deficits, and 17% (n = 5) suffered of pain. Fascicle biopsies were performed in 26 patients (87%). In four patients (13%), the tumor was completely resected and then reconstructed via nerve grafts. Seventy percent of the patients (n = 21) received a magnetic resonance imaging (MRI) within 5 years postoperatively, in which no progress was shown.Conclusions To diagnose perineurioma, it is essential to take a biopsy of an enlarged, nonfunctional fascicle. Furthermore, a long-distance epineuriotomy to decompress the hypertrophic fascicle is reasonable. To preserve the nerves' residual function, a complete resection is not recommended. Results after grafting are poor. One reason for this might be residual tumor cells along the nerve that cannot be visualized. Malignant transformation is not yet reported and tumor growth is stable for years.
Keywords: perineurioma; peripheral nerve sheath tumor; epineuriotomy; epithelial membrane antigen